Language technologies for the challenges of the digital age : 27th International Conference, GSCL 2017, Berlin, Germany, September 13-14, 2017, Proceedings /: 27th International Conference, GSCL 2017, Berlin, Germany, September 13-14, 2017, Proceedings. (2018) - Unknown
No abstract available